2005
DOI: 10.1182/blood-2005-03-1138
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mitochondrial respiration elevates oxygen concentration but leaves regulation of hypoxia-inducible factor (HIF) intact

Abstract: The transcription factor hypoxia-inducible factor-1 (HIF-1) is critical for erythropoietin and other factors involved in the adaptation of the organism to hypoxic stress. Conflicting results have been published regarding the role of the mitochondrial electron transport chain (ETC) in the regulation of HIF-1␣. We assessed cellular hypoxia by pimonidazole staining and blotting of the O 2 -labile HIF-1 ␣-subunit in human osteosarcoma cell cultures (U2OS and 143B). In conventional, gas-impermeable cell culture dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
91
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 50 publications
6
91
1
1
Order By: Relevance
“…In direct contrast to previous findings, some groups found that ρ° cell lines lacking functional mitochondria still stabilize HIFα under hypoxia [76,77]. Other studies suggested that cells with impaired mitochondrial function fail to stabilize HIFα under hypoxia, not because of defective ROS-generation, but because of intracellular O 2 re-distribution which leads to increased availability of O 2 as a substrate for the hydroxylation reaction [72,78].…”
Section: Role Of Ros In Cellular O 2 Sensingmentioning
confidence: 65%
“…In direct contrast to previous findings, some groups found that ρ° cell lines lacking functional mitochondria still stabilize HIFα under hypoxia [76,77]. Other studies suggested that cells with impaired mitochondrial function fail to stabilize HIFα under hypoxia, not because of defective ROS-generation, but because of intracellular O 2 re-distribution which leads to increased availability of O 2 as a substrate for the hydroxylation reaction [72,78].…”
Section: Role Of Ros In Cellular O 2 Sensingmentioning
confidence: 65%
“…This contrasts findings in mammalian cellular systems (e.g. human hepatoma cell lines) where the HIF-1a protein is detectable only under severe oxygen deprivation (1-0.1% oxygen) because PHD activity is compromised due to the lack of oxygen (Huang et al 1996;Doege et al 2005). Actually, the half-life of HIF-1a at atmospheric pO 2 in these cellular systems has been estimated to <5 min whereas its hypoxic stabilization happens instantaneously (Huang and Bunn 2003).…”
mentioning
confidence: 69%
“…However, Metzen and co-workers recently reported that under mild hypoxic conditions (3% O 2 ) chemical inhibition of mitochondria impaired hypoxic HIF-1α stabilization in normal cell culture dishes but not in oxygen-permeable dishes. Importantly, no difference was seen in severe (0.1% O2) hypoxia [45]. These data suggest that enough oxygen could be redirected from mitochondria (when the sink is blocked) towards the PHD oxygen sensors in mild hypoxia when the dishes (as usual) are gas-impermeable.…”
mentioning
confidence: 80%